1977
DOI: 10.5254/1.3535133
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Characterization of Polychloroprene Microstructure I. Spectral Assignments

Abstract: 13C NMR spectroscopy has proved to be a very powerful tool for the characterization of polychloroprene microstructure. We have identified and assigned the lines associated with diad and triad sequences involving the predominant trans-1,4 placement, together with other lines associated with cis-1,4, 1,2, isomerized 1,2, and 3,4 structural irregularities. Currently, we are performing 13C NMR, relaxation studies on the chloroprene polymers and will be presenting quantitative data in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…With the advent of 13 C nmr, a number of additional microstructures were observed. There was good agreement between earlier 1H nmr and 13 C nmr techniques (51,56,(60)(61)(62). Other studies of microstructure have been conducted with the aid of infrared and Raman spectroscopy (63,64).…”
Section: Polymersupporting
confidence: 68%
See 1 more Smart Citation
“…With the advent of 13 C nmr, a number of additional microstructures were observed. There was good agreement between earlier 1H nmr and 13 C nmr techniques (51,56,(60)(61)(62). Other studies of microstructure have been conducted with the aid of infrared and Raman spectroscopy (63,64).…”
Section: Polymersupporting
confidence: 68%
“…Unsymmetrical diene monomers such as chloroprene polymerize by four reaction pathways: 1,4 head-to-head, 1,4-head-totail, 1,2 and 3,4 polymerization. The concentrations of microstructure vary with polymerization temperature(51). The Z-or trans-configuration predominates at conventional polymerizations carried out in the range of 10 to 45 8C.…”
mentioning
confidence: 99%
“…Coleman and coworkers21–23 suggested the use of 13 C‐NMR to estimate the percentage of structural isomers in CR. A sample of Baypren 210 was dissolved in CDCl 3 and subjected to the 13 C‐NMR pulse sequence detailed by Coleman et al21 With corrections for the nuclear Overhauser effect in Coleman and Brame,22 it was estimated that the percentage of trans‐1,4‐units was 76.2%, the percentage of cis‐1,4‐units was 16.0%, the percentage of 1,2‐units was 1.45%, and the percentage of 3,4‐units was 1.75%. Coleman et al21 suggested that the resonance at 130.1 ppm was due to isomerized 1,2‐units.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably also the situation for a Data from Condon [1953], Richardson [1954], Pollock et al [1955]. b Data from Coleman and Brame [1978], Coleman et al [1977], Ebdon [1978]. …”
Section: -10a Radical Polymerizationmentioning
confidence: 90%